Ductal Carcinoma In Situ of the Breast - Vaidya, Yash (Indian J Surg, 2013)
Ductal carcinoma in situ (DCIS) of the breast is a potentially invasive neoplasm. Risk factors include high estrogen states such as use of oral contraceptive (OC) pills, nulliparity, advanced age at first birth, and also family history and genetic mutations. The incidence of this usually clinically silent condition has risen in the past few decades due to widespread screening and diagnostic mammography, with final diagnosis confirmed by biopsy. At present, treatment options include total or simple mastectomy or lumpectomy with radiation. Adjuvant therapy includes antiestrogens like tamoxifen and human epidermal growth factor receptor 2 (HER2) suppression therapy. With the latest advances in chemotherapy and better understanding on the pathogenesis of the lesion, it is anticipated that more effective modalities of treatment may soon be available.